2019
DOI: 10.1177/1078390319832965
|View full text |Cite
|
Sign up to set email alerts
|

Managing Shame: A Grounded Theory of How Stigma Manifests in Families Living With Dementia

Abstract: BACKGROUND: Alzheimer’s disease and related dementias are irreversible, progressive brain disorders that slowly destroy memory, language, problem solving, and cognition. In the United States, dementia is the fifth leading cause of death for people age 65 years and older. Early diagnosis could have important benefits stigma related to dementia remains a significant impediment to diagnosis, treatment, and accessing services. While a growing body of research documents the existence and negative outcomes of stigma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 39 publications
0
19
0
1
Order By: Relevance
“…The proportion is also lower than that found in other studies in Australia (88 %), Korea (97 %) and Taiwan (76 %) [17][18][19] The preference not to tell the diagnosis to the partner or spouse may be explained by negative attitudes towards dementia among a significant proportion of the Japanese community. Caregivers' shame associated with dementia causes stigma to people with dementia such as concealing, shunning, and silencing [27], with approximately 40-50 % of Japanese people having a prejudice that dementia is a shameful disease [28]. This finding might be a reflection of society's feelings towards people with dementia in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…The proportion is also lower than that found in other studies in Australia (88 %), Korea (97 %) and Taiwan (76 %) [17][18][19] The preference not to tell the diagnosis to the partner or spouse may be explained by negative attitudes towards dementia among a significant proportion of the Japanese community. Caregivers' shame associated with dementia causes stigma to people with dementia such as concealing, shunning, and silencing [27], with approximately 40-50 % of Japanese people having a prejudice that dementia is a shameful disease [28]. This finding might be a reflection of society's feelings towards people with dementia in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies provide robust evidence on the negative impact that stigma and discrimination has on people living with mental disorders more broadly 11–13. Although there is a paucity of research on the impact of stigma on people living with dementia,6 the existing evidence shows that stigma can lead to negative feelings about one self, shame, symptom and diagnosis concealment, negative social interactions, reduced access to care networks and social participation and even suicide 2 6 9 14–16. A global survey on attitudes towards dementia among members of the public, people living with dementia, family carers and healthcare professionals from 155 countries showed that over 85% of respondents living with dementia had their opinion not taken seriously as well as between 35% and 57% (in high-income countries and LMICs, respectively) had been treated unfairly in intimate relationships.…”
Section: Introductionmentioning
confidence: 99%
“…This cognitive decline probably starts years before the specific dementia diagnose is evident [1]. The persons lack of awareness in different areas such as cognitive decline, functional ability or social ability and changes in personality can make the diagnostic process complicated to handle [2] as well as the stigma that dementia has sometimes [3]. The prevalence of dementia in Sweden is estimated to 150 000 and predicted to double in 2050 and the cost is rising [4].…”
Section: Introductionmentioning
confidence: 99%